Reply to: Hasman A and Holm S. Nicotine conjugate vaccine: is there a right to a smoking future? - Cerny, T. (Journal of medical ethics, 2005)
A Hasman and S Holm have evaluated in a recent article in this journal1 the arguments in favour and against the preventive use of an antinicotine vaccine. This has been a timely article in view of the fact that at least three companies …